Pengaruh Perilaku Transfomational Leadership Kepala Sekolah Dasar Membangun Karakter Entrepreneurship Generasi Milenial Di SDN Kraton 6 (Eduscotech, 2024)
This study is motivated by the need to develop entrepreneurship character in elementary school students, particularly in facing the increasing global competition. The principal, by applying transformational leadership, is believed to play a crucial role in fostering entrepreneurial character in students. The main objective of this research is to examine the influence of transformational leadership of school principals on students' entrepreneurial character at SDN Kraton 6. This research uses a quantitative approach with a survey design, and data collection techniques include questionnaires, interviews, and observations. The findings indicate that the transformational leadership of the principal, particularly in idealized influence and individualized consideration, has a significant impact on the development of students' entrepreneurial character. These results show that principals who act as moral role models and provide individual attention to students can enhance creativity, independence, and risk-taking among students. This study concludes that transformational leadership is essential in shaping students' entrepreneurial character and suggests strengthening entrepreneurship programs based on real-life experience in elementary schools to further develop these characters in the future.